2015
DOI: 10.1039/c4cc09808k
|View full text |Cite
|
Sign up to set email alerts
|

Rapid (<3 min) microwave synthesis of block copolymer templated ordered mesoporous metal oxide and carbonate films using nitrate–citric acid systems

Abstract: Rapid chemical transformation from micelle templated precursors (metal nitrate and citric acid) to ordered mesoporous metal carbonates and oxides is demonstrated using microwave heating for cobalt, copper, manganese and zinc. Without aging requirements, <3 min of microwave processing yields highly ordered mesoporous films.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 18 publications
2
27
0
Order By: Relevance
“…2,5,7 Alternative nonequilibrium methods have been explored for the rapid formation of single crystal and polycrystalline inorganic nanostructures on shorter time frames. [20][21][22][23][24][25][26][27][28][29] For example, Tan et al demonstrated an all-laser-induced approach coupling BCP-directed self-assembly of resols with sub-millisecond laser heating (B-WRITE) to write hierarchically mesoporous polymer and carbon thin film structures. 21 Periodically ordered mesoporous crystalline silicon nanostructures were then obtained by filling the continuous network polymer template with amorphous silicon, followed by nanosecond laser-induced melt-crystallization and template removal.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…2,5,7 Alternative nonequilibrium methods have been explored for the rapid formation of single crystal and polycrystalline inorganic nanostructures on shorter time frames. [20][21][22][23][24][25][26][27][28][29] For example, Tan et al demonstrated an all-laser-induced approach coupling BCP-directed self-assembly of resols with sub-millisecond laser heating (B-WRITE) to write hierarchically mesoporous polymer and carbon thin film structures. 21 Periodically ordered mesoporous crystalline silicon nanostructures were then obtained by filling the continuous network polymer template with amorphous silicon, followed by nanosecond laser-induced melt-crystallization and template removal.…”
Section: Main Textmentioning
confidence: 99%
“…[21][22][23] Microwave annealing of mesoporous metal oxide thin films has been described but it required several minutes attaining limited crystallinity. 25 More recently, Hu et al and Tour et al reported a rapid Joule heating-based method generating discrete high-entropy metal nanoparticles, 26,27 sintered pellets of garnet ceramics with low porosity 28 and turbostratic graphene layers 29 on the milli-to tens of second timescales. We hypothesize pairing soft matter-directed self-assembly with Joule heating to form highly crystalline, wellordered mesoporous inorganic structures could open new pathways to access unique functional property profiles, expand parameter and application space, as well as develop new fundamental understanding of processing-structure-property correlations.…”
Section: Main Textmentioning
confidence: 99%
“…In general, rapid thermal annealing techniques using laser heating, radiation in rapid thermal processing, or microwave energy have been able to provide similar (or even better) ordering kinetics without the same EHS concerns . As such there has been significant interest in microwave annealing for DSA.…”
Section: Introductionmentioning
confidence: 99%
“…Since the discovery of mesoporous silica in 1990s, [13] ad iverse range of porous powders and films has been produced through hard-(e.g.,o rdered mesoporous silica, latex polymer beads) [14][15][16][17] and soft-templating (e.g.,s urfactants, triblock copolymers) [18][19][20][21][22][23][24][25] approaches. The templates can be removed by decomposition (calcination) with as tructuralt ension.…”
Section: Introductionmentioning
confidence: 99%